Central areolar choroidal dystrophy case - Tanrıverdi, Cafer; Nurözler Tabakçı, Burcu; Şentürk, Fevzi (Gazi Eye Foundation, 2020)
Central areolar choroidal dystrophy is a rarely seen, hereditary retinal disease which primarily affects macula. Here, we aimed to review clinical findings, ophthalmological imaging results and electrodiagnostic test results in a 43-years old man presented with visual impairment to our clinic and diagnosed as central areolar choroidal dystrophy.
Keywords: Dystrophy Case; Central Areolar Choroidal; Choroidal